Characterization of nanocellulose from oil palm empty fruit bunch: Effect of hydrothermal temperature - Alvika Meta Sari, .; Wan Azmi, Wan Hamzah; Anwar Ilmar, Ramadhan; Athiek Sri Redjeki, .; Yustinah, .; Zahra, Zain; Zibran Chairunisa, . (Semarak Ilmu Publishing, 2025)
The palm oil industry produces abundant solid waste, such as oil palm empty bunches (OP-EFB). This waste will cause environmental pollution when it is not utilized. It is a potential natural material for producing nanocellulose due to its high cellulose content. The most synthesized method of nanocellulose from oil palm empty fruit bunches is acid hydrolysis. However, this method will result in low yield and a multistage acid recovery process. To overcome this, this study was conducted using a modification method of ultrasonication–hydrothermal. This study aims to investigate the hydrothermal temperature effect on the properties of nanocellulose obtained from OP-EFB. The nanocellulose was prepared by alkali delignification, bleaching, and modification method of ultrasonication-hydrothermal at varied hydrothermal temperatures. After hydrothermal temperatures of 100 °C and 110 °C, nanocellulose was characterized by FTIR, SEM, and EDX. The result showed that the higher temperature will produce a higher nanocellulose yield. The optimum yield was obtained at 110 °C of 24.4%. However, the smallest size was obtained at 100 °C of 212.16 nm. The FTIR analysis indicated the removal of lignin and hemicellulose after the hydrothermal process. This study also showed how waste products from oil palm plantations can be utilized to produce nanocellulose, which is potentially applied in nanofluids.